TỔNG HỢP VÀ CHUYỂN HÓA MỘT SỐ DẪN XUẤT XETON-α,β-KHÔNG NO CHỨA 5-NITROFURFURAL - Hiền Anh, Nguyễn Thị; Triệu, Nguyễn Đình (Vietnam Journal of Chemistry, 2012)
By the condensation of 5-nitrofurfural diacetate (NFD) with aryl methyl ketone have been synthesized α,β-unsaturated ketones. These ketones have reacted with arylhydrazines to form hydrazones. The structure of these products  was confirmed by IR, UV, 1H-NMR and 13C-NMR  and Mass spectra.